The stabilisation of final focus system - Coe, P; Urner, D; Reichold, A (2007)
The StaFF (stabilisation of final focus) system will use interferometers to monitor the relative positions and orientations of several key components in the beam-delivery and interaction region. Monitoring the relative positions of the ILC final focus quadrupole magnets will be the most demanding application, where mutual and beam-relative stability will have a direct impact on machine luminosity. Established, laser-based frequency scanning interferometry (FSI) and fixed-frequency interferometry (FFI) offer positional resolution at length scales of the laser wavelength (1500 nm to 1560 nm) and a thousandth of the wavelength, respectively. As part of the ATF at KEK, StaFF will use interferometers to measure lines of a geodetic network to record relative motion between two beam position monitors. Interferometers are being designed and tested in Oxford prior to deployment at the ATF.